Social Values in the Tandak Sambas Dance in Sambas Regency West Borneo - Aditya, Mega Cantik Putri; Ismunandar, Ismunandar; Muniir, Asfar (Jurnal Pendidikan Sosiologi dan Humaniora, 2024)
One of the cultures owned by the Malay tribe is customs, beliefs and arts that are carried out as entertainment. Tandak Sambas dance is a traditional dance that functions as entertainment typical of the Malay tribe which still maintains its authenticity. It is necessary to make protection efforts carried out by the state to avoid violations of the Sambas Tandak dance from cultural claims by other countries. The creator of the Sambas Tandak dance movement or choreography of the dance has also not been registered as copyright. Tandak Tambas dance is included in the form of traditional dance (folk dance). Tandak Sambas dance, functions as a means of performance, here dance is useful for entertaining the wider community. This dance comes from a folk game that is very close to the development of community life from various aspects. One of the values contained in the sustainability of Sambas tandak dance performances is social values. The social values of the Malay indigenous people are reflected in several changes and also the overall performance form. By trying to research this, it is hoped that the social values contained in this dance will not be lost and can still be maintained from generation to generation in the Malay indigenous community, especially in the Sambas Regency area.